2020
DOI: 10.3389/fimmu.2020.01800
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Changes of Adipokine and Cytokine Secretion From Rat Adipose Tissue by Endogenous and Exogenous Toll-Like Receptor Agonists

Abstract: White adipose tissue but recently also brown adipose tissue have emerged as endocrine organs. Age-associated obesity is accompanied by prolonged and elevated lipopolysaccharide (LPS)-induced sickness symptoms and increased cytokine and adipokine levels in the circulation partially originating from adipose tissue. In the present study, ex vivo fat explants were used to investigate how the exogenous pathogen-associated molecular pattern (PAMP) LPS or the endogenous danger-associated molecular patterns (DAMPs) hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 120 publications
1
20
0
1
Order By: Relevance
“…In osteoarthritis and other inflammatory disorders, fat pads contribute to the generation of adipokines and cytokines. This study and a previous study ( 57 ) demonstrated that adipokines regulate osteoarthritis and bone remodeling. This study’s GSEA analysis revealed that osteoarthritis was linked to graft-versus-host disease and Leishmania protozoa infection, which was one of the study’s findings.…”
Section: Discussionsupporting
confidence: 82%
“…In osteoarthritis and other inflammatory disorders, fat pads contribute to the generation of adipokines and cytokines. This study and a previous study ( 57 ) demonstrated that adipokines regulate osteoarthritis and bone remodeling. This study’s GSEA analysis revealed that osteoarthritis was linked to graft-versus-host disease and Leishmania protozoa infection, which was one of the study’s findings.…”
Section: Discussionsupporting
confidence: 82%
“…The analysis of PPI interactions indicated six key modules ( Table 1 ), and 10 molecules were the most significant, including COMP, COL1A1, STAT3, HAPLN1, HBEGF, CCL2, MMP13, SMAD4, CXCL1, and CTSK. We noticed that these enriched activities of immune responses, TNF signaling pathway, and cytokine-cytokine receptor interaction could be regulated by Tlr molecules ( Peek et al, 2020 ). At the same time, Tlr2 and Tlr4 disrupted the SGN degeneration signaling network ( Figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…Interscapular BAT was dissected after skin disinfection (70% ethanol; Stockmeiern) and explant cultures had been performed as recently described with small modifications to account for the high energy needs of this highly metabolic tissue. 61 In brief, for each independent experiment, BAT from eight mice was washed with cold PBS (Capricorn Scientific), cut into ~40 mg pieces to ensure nutrient supply, and stored on ice in oxygenated Earle’s balanced salt solution (Thermo Fisher Scientific) supplemented with penicillin–streptomycin (100 U/mL, Thermo Fisher Scientific), and 20 mM HEPES (Sigma-Aldrich). For each experiment, eight wells of BAT were cultured in 12-well plates with DMEM supplemented with high glucose (GlutaMax Supplement, Thermo Fisher Scientific) containing 10% FBS (Capricorn), penicillin–streptomycin (100 U/mL), and 40 mM HEPES for 2 hours at 37°C (95% humidity, 5% CO 2 , and 95% air).…”
Section: Methodsmentioning
confidence: 99%
“…BAT-explant cultures have been used to investigate cytokine release into supernatants. 61 After collection of the supernatants, BAT was frozen on dry ice and stored at −80°C for further analyses of UCP1 expression.…”
Section: Methodsmentioning
confidence: 99%